The Relationship of Community Knowledge and Attitude with Action to Keeping The Cleaning of The River Flow - Ukat, Adiyosi Destio (Faculty of Public Health, Nusa Cendana University, 2024)
Community knowledge and attitudes can significantly influence public actions in maintaining the cleanliness of river basins. Good knowledge about river basins (DAS) can foster awareness and promote positive attitudes toward preserving river cleanliness. This study aims to understand the relationship between community knowledge and attitudes regarding the cleanliness of the Osmo Batugang River Basin in Alak Subdistrict, Kupang City. Data were collected through interviews. The data analysis employed descriptive and bivariate methods. The results revealed a significant correlation between knowledge and actions to maintain river cleanliness (p = 0.046 < 0.05), as well as a significant relationship between community attitudes and actions to maintain river cleanliness (p = 0.000 < 0.05). Based on these findings, river basin issues should be considered for appropriate intervention to address cleanliness problems in the community environment. Furthermore, information regarding the importance of maintaining river cleanliness can serve as a source to enhance community understanding, which in turn can contribute to improving the health of communities living along riverbanks.